3D Page-Flipped Worksheet on Impulse-Momentum to Develop Students' Scientific Communication Skills (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
Students’ developmental skills, including critical thinking skills, problem-solving skills, creativity, metacognitive skills, communication skills-collaboration, digital literacy-technology are integrated into current issues discussed at the 21st-century skills. Utilization of digital technology as media and learning resources reflects a transition of X generation to Y generation learners. The use of digital technology in learning can be an excellent opportunity to improve the 21st-century skills, particularly in the development of scientific communication skills in learning physics. This study employed 3D Page-Flipped Worksheet on impulse and momentum to improve students’ scientific communication skills. This research belongs to a developmental study with 4D development model covering Define, Design, Develop, and Disseminate. The subjects were students senior high school grade X in Yogyakarta. The results showed that 72.5% of students had excellent verbal communication skills, and 65.6% had good written communication skills. Based on the results, the use of 3D Page-Flipped Worksheet is successful in constructing the students’ understanding and communication skills, both oral and written.